Analysis of Fatty Acids of Liver in the Embryo and Adult of Domesticated Chicken Gallus Gallus Domesticus - Nahla A. Al-Bakri (Journal of Global Pharma Technology, 2016)
The fatty acids in the embryo's liver at ages (7, 11, 14 and 19) days incubation, small chicken aged (14) days after hatching and adult were analyzed, and found (5) fatty acids, the highest concentration of fatty acid in the adult of domesticated chicken and lowest concentration in small chicken age (14) days after hatching. Statistically, there were high significant differences at the probability level (P≤0.001) between all ages together, and the highest concentrations of Oleic acid (C18:1) and Linoleic acid (C18:2) were in embryo age (7) days incubation, while in embryo age (11) days incubation Stearic acid (C18:0) and α-Linolenic acid (C18:3) were higher concentration and Palmitic acid (C16:0) was the highest concentration in the adult. Stearic, Palmitic, Linoleic and α-Linolenic acids were recorded as the lowest concentration as well as in a small chicken age (14) days after hatching. Oleic acid had the lowest concentration in the embryo (19) days incubation, as well as α-Linolenic acid in the embryos age (7, 19) days incubation and the adult chicken did not record any concentration.Key words: Fatty acid, Chicken, Embryo, Liver.